Pengembangan Majalah untuk Menumbuhkan Kemampuan Berpikir Kausalitas di SMA - Ranti Pebriani; Zafri Zafri; Ofianto Ofianto (RC-INSTITUT, 2019)
This research aims to determine the practicality of the use and feasibility of magazines in fostering the ability to think of causality in high school students on material efforts to maintain independence from the threat of the Allies and the Netherlands. The method used in this research is R & D research (Research and Development) which aims to produce a certain product and has been tested its effectiveness. Trial-test conducted in SMA N 2 Padang. While the time of research is in May - July 2017. The development step using 4D Thiagarajan, Semmel, and Semmel (1974) model consists of define, design, development, disseminate. The subjects of the research were students of SMA N 2 Padang class XI IPA 2, amounting to 36 people. The instrument of data collection using a questionnaire in the form of a Likert Scale. This scale is structured using the positive category with the highest score of 5 to strongly agree and 1 category strongly disagrees. The data analysis technique used is descriptive quantitative. The results showed that the assessment of the material expert's validator said the magazine is very feasible to use with data analysis of 4.6. While the expert magazine's validator obtained a score of 4.1. After that, the magazine is tested to the students. After a trial-test conducted with the results of 61% of the students are in a good category. Furthermore, the results of calculating using product moment, shows r count 0.635 this figure shows the relationship of magazines and think causality is significant (high). This magazine developed to improve the ability to think the causality of learners declared feasible and can improve the ability to think causality, so that can be utilized by teachers in learning history.